THE RELATIONSHIP OF VITAMIN D TOPOLYCYSTIC OVARY SYNDROME (PCOS) TEENAGERS AT KOTO TANGAH PADANG DISTRICT HIGH SCHOOL IN 2022 - Hardi Cahyo Utomo; Haviz Yuad; Ida Rahmah Burhan (Andalas Obstetrics And Gynecology Journal, 2024)
PCOS is characterized by increased ovarian and adrenal androgen secretion,hyperandrogenic symptoms such as hirsutism, acne and/or alopecia, menstrual irregularities,and polycystic ovaries. The prevalence of PCOS in 2016 was 6âˆ’21% of reproductive ageworldwide. PCOS is the most common female endocrine disorder with a prevalence of around4-6% in women of reproductive age in Indonesia. Vitamin D deficiency can increase PCOSsymptoms. The research design was cross-sectional. The study was conducted at SMA N 7,SMA N 8 and SMA N 13 Padang in Koto Tangah District in May-August 2022. The researchsample was high school students who experienced menstrual cycle disorders and were willingto agree to informed consent for the study with a sample size of 59 respondents. Vitamin Dlevels were examined using the 25-Hydroxyvitamin D ELISA Kit. Data were analyzed by chi-square test. The results showed that 86.4% of respondents experienced vitamin D deficiency.Statistically there was a relationship between PCOS in adolescents accompanied byhyperandrogens and vitamin D levels, there was a relationship between PCOS in adolescentsaccompanied by obesity and vitamin D levels, there was no relationship between PCOS inadolescents accompanied by acanthosis nigrican and vitamin D levels, and there was norelationship between PCOS in adolescents accompanied by hyperandrogens, obesity andacanthosis nigrican with vitamin D levels in SMA Koto Tangah District Padang in 2022. Theconclusion of this study is that there is a relationship between PCOS in adolescentsaccompanied by hyperandrogens and vitamin D levels and there is a relationship betweenPCOS in adolescents accompanied by obesity and vitamin D levels. .